Hypertension as Comorbidity in Pemphigus Vulgaris Patients: A Case Series - Bobby Febrianto; Lian Kamilah; Fanny Fauziyyah Heryadi; Azhar Arrosyid; Nurrachmat Mulianto (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Pemphigus Vulgaris (PV) is a chronic autoimmune bullous disease characterized by flaccid blisters on the skin and mucous membrane. This study aimed to report a serial case of PV followed by hypertension as comorbidity. Case presentation: Four patients, 2 males, and 2 females were hospitalized due to PV. All of these patients also suffer from hypertension, but only 2 patients take antihypertension. Drugs relatively, histopathology features of all patients revealed a cleft above the basal epidermal layer with a tombstone appearance. Pemphigus vulgaris can be accompanied by hypertension as comorbidity, but its pathogenesis is unclear. A low level of programmed cell death 1 (PD1) in PV patients promotes downregulating protective factors, including T regulator (Treg) cells. In addition, decreasing the PD1 level may cause apoptosis and inflammation process in the vascular endothelial, which may lead to hypertension. Conclusion: Pemphigus vulgaris is significantly associated with hypertension.